PERBEDAAN TINGKAT KESEGARAN JASMANI SISWA PUTRA KELAS VII SMP NEGERI 6 DESA TELUK DENGAN SISWA PUTRA KELAS VII SMP NEGERI 1 KECAMATAN KUALA KAMPAR - Romanto, Romanto; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: From the observations it was found that the lack of knowledge and so on that the researchers saw did not interfere with the level of physical fitness they possessed and this clearly revealed the function of the heart, lungs, blood circulation or their physical fitness was very good, and this became one of the problems background of this research because according to healthy researchers not only formed from clean words but how supporting factors are able to maintain and give a big influence on the physical fitness of people or students who are in it. The purpose of this study that is very much wanted to be achieved is to find out how the differences in the physical fitness level of male students of class VII of Teluk 6 Middle School with male students of class VII of Kuala Kampar State Middle School 1. As for the population in this study as many as 63 people and used Random Sampling to determine the sample as many as 26 people. The instrument used in this study was the Indonesian Physical Fitness Test for adolescents aged 13-15 years. Based on the data from the physical fitness test results of class VII male students of Teluk 6 Middle School 6 there were no excellent scores or above 22 of the respondents namely 0%, well classified 18-21 there were 6 respondents namely 46.15% of the respondents classified while 14-27 there are 7 respondents, namely 53.84% while the classification is lacking and there are very few respondents or 0%. Meanwhile for the data on the classification results of the physical fitness test for male students at SMP Negeri 1 Kuala Kampar Subdistrict, there was no value at all or above 22 from respondents, namely 0%, on good calcifications 18-21 from respondents 0%, then medium calcifications 14-17 there were 12 respondent or 93.30% while the classification is less there is 1 respondent or 7.69% while the classification is less or 0%. From the above explanation can also be drawn the final conclusion "That the level of physical fitness of male students of Class VII SMP Negeri 6 Desa Teluk is better, than students of the seventh grade students of SMP Negeri 1 Kuala Kampar District".Key Words: Application, Level of Physical Freshness